OP0068 ABATACEPT IN EARLY DIFFUSE CUTANEOUS SYSTEMIC SCLEROSIS— RESULTS OF A PHASE 2 INVESTIGATOR-INITIATED, MULTICENTER, DOUBLE-BLIND RANDOMIZED PLACEBO-CONTROLLED TRIAL. (June 2019) - Khanna, Dinesh; Spino, Cathie; Bush, Erica; Johnson, Sindhu; Chung, Lorinda; Denton, Christopher; Molitor, Jerry; Steen, Viginia; Lafyatis, Robert; Simms, Robert; Kafaja, Suzanne; Frech, Tracy; et al.
Abstract : Background: Abatacept (ABA) is a recombinant fusion protein including extracellular domain of human CTLA4 and hinge– CH2–CH3 of the Fc domain of human IgG. Objectives: This phase 2 trial assessed the safety and efficacy of ABA 125 mg subcutaneous (SC) versus placebo SC given every week on skin fibrosis using the modified Rodnan skin score (mRSS) in diffuse cutaneous SSc (dcSSc; clinicaltrials.gov NCT02161406 ). Methods: A 12-month, investigator-initiated, multicenter double-blind, randomized placebo-controlled trial was conducted between September 2014 and February 2018 at 27 US, Canadian and UK sites. Eligible subjects were randomized in a 1:1 ratio to either ABA or matching placebo, stratified by duration of dcSSc (≤18 vs >18 to ≤36 months). Key inclusion criteria included dcSSc with disease duration of ≤ 36 months (defined as first non−Raynaud phenomenon) and mRSS ≥ 10 and ≤ 35 units for disease duration of ≤ 18 months and mRSS ≥ 15 and ≤ 45 units with evidence of active disease for disease duration of >18-36 months. Escape therapy was allowed at 6 months for worsening SSc. Primary outcomes include safety and change in mRSS over 12 months (ΔmRSS). Secondary endpoints include ΔFVC%, ΔHAQ-DI, Δpatient and Δphysician global assessment, and ACR CRISS 1 (composite measure in dcSSc). The primary endpoint of ΔmRSS was assessed using a linear mixed model (see Table) with primary end point data censored after initiation of escape therapy. Results: 88 subjects were randomized (44/group) and formed the mITT group; 34 (77%) and 35 (80%) completed the 12-month double-blind treatment period in ABA and placebo groups, respectively. At baseline, the mean age was 49 years, 75% were female, mean disease duration was 1.59 years, 60% had disease duration ≤ 18 months, mRSS was 22.4, mean FVC% was 84.3%, and mean HAQ-DI was 1.0. Compliance with both drugs was >98%. ABA was well tolerated with comparable adverse events (AEs), serious AEs, and AEs of special interest (e.g., infections and malignancies) between treatments. There were 3 deaths during the treatment— 2 in ABA (both scleroderma renal crisis-days 11 and 46) and 1 in placebo (sudden cardiac arrest- day 310). The primary endpoint showed an adjusted mean improvement of mRSS of -6.24 in ABA vs. -4.49 in placebo, p= 0.28 (Table). The secondary outcome measures were statistically significant and clinically meaningful (HAQ-DI and physician global assessment) or showed numerical results favoring ABA (Table). A larger proportion of placebo subjects required escape immunosuppressive therapy vs. ABA (36% vs. 16%, p=0.03). Estimates are from a linear mixed model with treatment group, month (3, 6, and 12), treatment x month interaction, duration of dcSSc (≤18 vs >18 to ≤36 months), and baseline outcome measure as fixed effects and participant as a random effect (except for ACR CRISS). For ACR CRISS, treatment differences were assessed by the non-parametric Van Elteren test. Multiple imputation was used for ACR CRISS analysis. Conclusion: In patients with early dcSSc, ABA was well tolerated, but ΔmRSS was not statistically significant. Secondary outcome measures showed evidence in favor of ABA, including greater requirement of escape therapy in the placebo group. mRSS showed large variability, despite recruiting an early dcSSc population. References: [1] Khanna D, et al. Arthritis Rheumatol2016, 68:299-311 Acknowledgement: Project was supported by NIH/NIAID Clinical ACE grant (5UM1AI110557-05) and an investigator-initiated grant by Bristol-Myers Squibb. Disclosure of Interests: Dinesh Khanna Shareholder of: Eicos Sciences, Inc, Grant/research support from: Bayer, BMS, Pfizer, Horizon, Consultant for: Actelion Acceleron, Arena, Bayer, BI, BMS, CSL Behring, Corbus, Cytori, GSK, Genentech/Roche, Galapagos, Employee of: Elcos Sciences, Inc, Cathie Spino: None declared, Erica Bush: None declared, Sindhu Johnson: None declared, Lorinda Chung Grant/research support from: United Therapeutics, Consultant for: Reata, Bristol Meyers Squibb, Boehringer Ingelheim, Mitsubishi Tanabe, Eicos, Christopher Denton Grant/research support from: GlaxoSmithKline, Inventiva, CSF Behring, Consultant for: Roche-Genentech, Actelion, GlaxoSmithKline, Sanofi Aventis, Inventiva, CSL Behring, Boehringer Ingelheim, Bayer, Jerry Molitor Grant/research support from: Pfizer, Consultant for: Boehringer Ingelheim, Amgen, Viginia Steen Consultant for: CSL Behring, Corbus and Bayer, Paid instructor for: Advisory Board: CSL Behring, Roach, Bayer and Reata, Robert Lafyatis Grant/research support from: Kiniksa, Elpidera, Regeneron, PRISM biolab, Consultant for: Sanofi, Genentech, Formation, Biocon, Bristol Meyers Squibb, Merck, Robert Simms: None declared, Suzanne Kafaja: None declared, Tracy Frech: None declared, Vivian Hsu: None declared, Robin Domsic Consultant for: Eicos Sciences Inc/Civi Biopharma and Boehringer-Ingelheim., Janet Pope Consultant for: Eli Lilly and Company, Jessica Gordon Grant/research support from: Corbus Pharmaceuticals Cumberland Pharmaceuticals, Maureen Mayes Grant/research support from: Maureen Mayes is a clinical trial investigator for Boehringer-Ingelheim; Galapagos, Reata, Sanofi, Merck-Serono, Consultant for: Maureen Mayes is a member of scientific advisory boards for Galapagos NV (Pharma), Boehringer-Ingelheim, Mitsubishi-Tanabe, Astellas: Grant Review Board for Actelion., Speakers bureau: Maureen Mayes received personal fees for being a conference speaker on the use of autoantibodies in connective tissue diseases for Medtelligence, Elena Schiopu Grant/research support from: Bristol Meyers Squibb and Bayer, Amber Young: None declared, Nora Sandorfi: None declared, Jane Park: None declared, Faye Hant: None declared, Elana Bernstein Grant/research support from: I have an investigator-initiated research grant from the Pfizer ASPIRE Rheumatology Program., Consultant for: I am the medical monitor for SLS III, which is sponsored by Genentech, Soumya Chatterjee: None declared, Flavia Castelino Consultant for: Genentech, Boehringer, Ali Ajam Consultant for: Focus Point Global, Yannick Allanore Grant/research support from: Inventiva, F Hoffman La-Roche, Sanofi, BMS, Pfizer, Consultant for: Actelion, Bayer, BMS, Boehringer, Roche, Sanofi, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders, Ora Gewurz-Singer: None declared, David Fox Grant/research support from: Regeneron, Gilead, Seattle Genetics, Consultant for: Grant reviewer for Pfizer, Daniel Furst Grant/research support from: F. Hoffmann-La Roche, Genentech